Initial experience with robotic technology for thoracic surgery using the da Vinci Xi system in Tibet, China - Ping, Ni; Baoguo, Zhou; Renqing, Zhaxi; Shaodong, Wang (Frontiers in Surgery, 2024)
Objective Although the robotic surgical system has accumulated rich experience in the development of thoracic surgery, its application in Tibet area is relatively late. We report our experience concerning da Vinci Xi system in thoracic surgery and observe its practicability and surgical effect. Methods We retrospectively analyzed 26 patients who underwent robotic thoracic surgery including: twelve lung resection, two esophagectomies, ten mediastinal surgeries and two rib mass resection. The data of patient characteristics, operative time, perioperative complications were collected. Results Of the 26 patients, 22 cases were completed with da Vinci system successfully, including 7 segmentectomies, 4 lobectomies, 1 subsegmentectomy, 2 esophagectomies, 10 mediastinal surgeries (6 thymic resections, 3 posterior mediastinal tumor resection, 1 mediastinal cyst resection) and 2 rib mass resection. In which, 3 cases of lung resection begun with robotic technique were converted to thoracoscopic surgery (due to calcification of hilar lymph node), 1 case of bilobectomy was converted to thoracotomy due to thoracic adhesion. All the operations went well and no patients need blood transfusion. All patients had satisfactory postoperative recovery. Conclusion It is safe, reliable and effective to carry out robotic thoracic surgery on the plateau. On the premise of carefully and seriously discussing the indications of surgery, we should actively carry out the application of da Vinci robotic surgery system in Tibet Plateau.